Formalizing natural languages with NooJ and its natural language processing applications : 11th International Conference, NooJ 2017, Kenitra and Rabat, Morocco, May 18-20, 2017, revised selected papers /: 11th International Conference, NooJ 2017, Kenitra and Rabat, Morocco, May 18-20, 2017, revised selected papers. (2018) - Unknown
No abstract available